1996
DOI: 10.1063/1.117366
|View full text |Cite
|
Sign up to set email alerts
|

Defect and transport properties of nanocrystalline CeO2−x

Abstract: It is shown that unique defect thermodynamics and transport properties result for oxides of a few nanometers crystallite size. Fully-dense CeO2−x polycrystals of ∼10 nm grain size were synthesized, and their electrical properties compared with those of samples coarsened from the same material. The nanocrystals showed reduced grain boundary resistance, 104 higher electronic conductivity, and less than one-half the heat of reduction of its coarse-grained counterpart. These properties are attributed to a dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
244
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(268 citation statements)
references
References 6 publications
24
244
0
Order By: Relevance
“…For catalytic applications CeO2 has to be grown on metallic substrates, but few studies exist on cerium oxide film deposited on metals and most of them have the aim to depict the epitaxial growth [6 and references therein]. CeO2 deposition is achieved by using a variety of growth techniques [7,8,9,10]. When highly stoichiometric oxide is required, atomic layer deposition (ALD) is the most suitable technique.…”
Section: Introductionmentioning
confidence: 99%
“…For catalytic applications CeO2 has to be grown on metallic substrates, but few studies exist on cerium oxide film deposited on metals and most of them have the aim to depict the epitaxial growth [6 and references therein]. CeO2 deposition is achieved by using a variety of growth techniques [7,8,9,10]. When highly stoichiometric oxide is required, atomic layer deposition (ALD) is the most suitable technique.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of re-adsorption, a desorption peak temperature of 623 K would correspond to an activation energy for desorption of roughly 200 kJ/mol of O 2 , compared to the tabulated value for the oxidation enthalpy for Ce 2 O 3 of -760 kJ/mol-O 2 [25]. Third, electrical conductivity measurements have indicated that the enthalpy of reduction for ceria nano-particles is half that of bulk ceria [26,27]. Finally, Rodriguez and coworkers used X-ray Near Edge Spectroscopy and other techniques to suggest that ceria and ceria-zirconia nano-particles reduce more easily [28].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that samples sintered at 1400°C showed higher oxygen conductivity than those sintered at 1500°C, and argued that larger density of grain boundaries in 1400°C samples provided more area for the dopants to segregate for a given concentration of dopants. Eventually dopant segregation could cause depletion in the oxygen vacancy concentration in the vicinity of the grain boundaries as per the space-charge layer model, 101,102 thus reducing the overall conductivity. Thus, in view of these experimental observations, it appears that instead of the blocking effect of grain boundaries, larger focus may be required on preventing dopant segregation.…”
Section: Effect Of Dopant Segregation On Oxygen Energeticsmentioning
confidence: 99%
“…They performed diffusivity measurements using MD simulations on four dislocations, i.e., [100]{110}, [110]{110}, [101]{110} and a screw dislocation. Surprisingly, in all four dislocations, they observed enhancement in oxygen diffusivity, and the activation energies were significantly lower than those in the bulk.…”
Section: Misfit Dislocationsmentioning
confidence: 99%